PERAN GURU PAI DALAM PEMBINAAN AKHLAK SISWA DI SDN PENGGARON MOJOWARNO JOMBANG - Budiyono, Ahmad; Rahman Hakim, Arif; Hidayatulloh, Arif (ILJ: Islamic Learning Journal, 2023)
Fostering morals in children is something that must be considered by parents, teachers and the community in order to produce the next generation of people who are noble and knowledgeable. Therefore the role of the PAI teacher is very important, because the role of the PAI teacher is all religious efforts made to develop religious potential in order to achieve the goals of Islamic education. This study discusses moral development carried out by Islamic religious education teachers towards their students at Penggaron Elementary School. This research is a field research (field research), the form of research is descriptive qualitative with the design of data collection techniques through interviews, observation and documentation. Furthermore, data analysis was carried out using descriptive qualitative analysis. The results of the study found that the role of PAI teachers in fostering student morals included: providing exemplary students, habituating religious activities, giving advice and giving sanctions or punishments to students who violated it. The morals possessed by Pengaron Elementary School students include: Religious, disciplined, polite, responsible, fond of reading, honest. In the process of fostering student morals, supporting and inhibiting factors were found for the teacher in fostering student morals. Among the supporting factors for PAI teachers in fostering student morals is the existence of cooperation between PAI teachers and all school members. Meanwhile, the inhibiting factor is the environmental factors that are different for each student, making it difficult for the school to supervise each student when they are out of school.